A transmigração da causalidade no Fédon de Platão - Sobrinho, Rubens G. Nunes (Revista Archai, 2015)
Abstract: In the dialogue that shows the last philosophical speech of Socrates, Plato examines the theme of death: Socrates explores the tradition of Mysteries to find images that may justify his unusual attitude towards death. The very definition of death presupposes the existence and survival of the soul. Without defining the soul, Plato reconfigures the axioms based on the heterogeneity of the Mysteries. This reconfiguration of ancient beliefs results in the causal transmigration that moulds the hypothesis of Forms. The composition of the final myth is the results on a long dialectical pursue which re-establishes the discursive reason of images qualified as a “noble risk” (‘ÎºÎ±Î»á½¸Ï‚’, Phd. 114d6). The aim of this analysis is thus to identify the itinerary by which the ‘noble risk’ of palingenesis constructs the axiom and the causal principle of Forms as the explanation of truth and the nature of all beings. Keywords: Causality, Forms, Participation, Palingenesis.